En los márgenes de la lingüística celta: los etnónimos del noroeste de la Península Ibérica y una ley fonética del hispano-celta occidental (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
A whole series of ethnic names attested in the NW of the Iberian peninsula, all of which apparently bear an otherwise unknown  suffix –urro- or –arro-, is best explained if we admit a new Hispanic-Celtic sound change, whereby a segment –ry- regularly yields –rr- in an area roughly coincident with the realms of the northernmost Asturian populations. A relationship between the names Arrōnī, MIr. Airem and the lepontic dative plural Ariuonepos is established on the basis of a nomen agentis *aryo-mon- “ploughman”.
Keywords: Indo-European; Ethnic Names; Place Names; Celtiberian; Epigraphy